VOCATION VERSUS PROFESSION. - McClay, Wilfred M. (Fides et historia, 2017)
The article offers the author's response to Jay Green's book "Christian Historiography: Five Rival Versions." The author expresses his admiration to the way Green self-consciously embraced a vocation as a historian rooted in a single institution, the Covenant College in Lookout Mountain, Georgia. He also says that the book reinforces the advantages Christian historians have over their secular peers.